2015
DOI: 10.4018/ijcallt.2015100101
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-based Extensive Reading

Abstract: Mobile devices have sweeping repercussions in education and suggest shifting content-engagement paradigms. Extensive reading (ER) is not unaffected by the many evolving aspects of mobile technology in second language classrooms. This paper reflects on Xreading®, an online graded reader (GR) and learning management system (LMS) designed for digital ER. Students at a private university in Tokyo had access to this online library using mobile devices. While overall reflections were positive, actual engagement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Extensive reading provides an opportunity for language learners to choose the reading preferences based on their ability to read English texts. Day and Bamford in Milliner and Cote (Milliner & Cote, 2015) argue that extensive reading allows students to read large quantities of self-selected reading materials that are below or at their language level. In this activity, they are encouraged to choose their texts without any coercion from the teacher when choosing their reading source.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive reading provides an opportunity for language learners to choose the reading preferences based on their ability to read English texts. Day and Bamford in Milliner and Cote (Milliner & Cote, 2015) argue that extensive reading allows students to read large quantities of self-selected reading materials that are below or at their language level. In this activity, they are encouraged to choose their texts without any coercion from the teacher when choosing their reading source.…”
Section: Introductionmentioning
confidence: 99%
“…Language learners can choose their reading preferences based on their ability to read English texts through ER. In Milliner and Cote (Milliner & Cote, 2015), Day and Bamford suggest students who choose to participate in extensive reading are given the opportunity to read considerable amounts of material that is either below or at their current language level. Students are given the freedom to select the readings that they want to do for this assignment without any interference from the lecturer.…”
Section: Er In Efl Classroommentioning
confidence: 99%
“…The study reported that the students benefited pronunciation, prosody and intonation improvement. Meanwhile, Milliner and Cote (2015) introduced digital-mediated ER project to their university students through which the students were engaged in ER program through mobile devices. Their study pointed out the pedagogical implication which emphasized on the importance of software training and ER practice.…”
Section: Introductionmentioning
confidence: 99%